MANAJEMEN DANA IURAN RUKUN KEMATIAN DI PUNTUN KOTA PALANGKA RAYA - Jirhanuddin Jirhanuddin; Ahmad Dakhoir; Sulistyaningsih Sulistyaningsih (AL-QARDH, 2016)
The existence of rukun kematian (RKM) nowadays is extremely helpful for the society. Therefore, it needs a good management in order to make RKM running well and functioning as the purpose when it was established. However, the result of observation toward RKM Puntun, Palangka Raya showed several inexpediencies about the application of management elements and the distribution of compensation that given by RKM. Then this research discussed about funding management and compensation practices by RKM to its member. There were two problems of the study: (1) How is the funding management in RKM in Puntun, Palangka Raya, (2) Is the distribution of compensation appropriate with ta’awun principal.            This research used qualitative-descriptive approach which the object of the study was funding management of RKM Puntun, Palangka Raya and appropriate distribution of compensation with ta’awun principal. Meanwhile, the subject of the study consisted of 3 board members. Collecting data method was used observation, interview, and documentation. Whereas, data validation was proven with triangulation technique then analyzed with collection, reduction, display, and conclusion method.            Through various reference of theory that was used in order to support the study. The result of funding management of RKM Puntun, Palangka Raya was not fully applied the management elements. Afterwards, the distribution of compensation of RKM was not fully applied ta’awun principal as well. This can be seen when parties from RKM provides a perind for 3 months against members of the new register, in a period of 3 months before new members receive accident (died), then the member is not entitled to receive compensation from the RKM.